Moral Philosophy of Selimbur Caye Oral Tradition and Its Relevance to Character Education in Indonesia - Irwan Satria; Een Syaputra; Ririn Selvianti (UIN Fatmawati Sukarno Bengkulu, 2022)
article aims to identify moral philosophy contained in Selimbur Caye oral tradition and analyze the relevance of the moral philosophy to character education in Indonesia. This research used qualitative descriptive method. Object of this study is Selimbur Caye oral tradition. The data was collected using in-depth interview, participatory observation, and documentation. They were analyzed using Miles and Huberman’s interactive model of qualitative data analysis. Based on the analytical result, there are two main categories of moral philosophy contained in Selimbur Caye oral tradition; respect and responsibility. Later, in this study, the two main philosophies are derived into several foundation/supportive moral values such as sportsmanship, tolerance, democracy, discipline, honesty, fairness, wisdom, loyalty, professionalism, trustworthiness, social care, co-operation, social solidarity, and friendship. Another result found is that those philosophies are strongly relevant to the character education values developed by Indonesian ministry of education and culture: 1) fairness; 2) tolerance; 3) democracy; 4) friendly/communicative; 5) love peace; 6) social care, and 7) responsibility.